Resonant Moments in Media Events: - Josephine Lukito; Prathusha Sarma; Jordan Foley; Aman Abhishek; Erik Bucy; Larissa Doroshenko; Zhongkai Sun; Jon Pevehouse; William Sethares; Dhavan Shah (Journal of Quantitative Description: Digital Media)
Live-tweeting has emerged as a popular hybrid media activity during broadcasted media events. Through second screens, users are able to engage with one another and react in real time to the broadcasted content. These reactions are dynamic: they ebb and flow throughout the media event as users respond to and converse about different memorable moments. Using the first 2016 U.S. presidential debate between Hillary Clinton and Donald Trump as a case, this paper employs a temporal method for identifying resonant moments on social media during televised events by combining time series analysis, qualitative (human-in-the-loop) evaluation, and a novel natural language processing tool to identify discursive shifts before and after resonant moments. This analysis finds key differences in social media discourse about the two candidates. Notably, Trump received substantially more coverage than Clinton throughout the debate. However, a more in-depth analysis of these candidates’ resonant moments reveals that discourse about Trump tended to be more critical compared to discourse associated with Clinton’s resonant moments.